The Role of Hypoxia Inducible Factor-1 in Hepatocellular Carcinoma. (2nd July 2014) - Luo, Dongjun; Wang, Zhongxia; Wu, Junyi; Jiang, Chunping; Wu, Junhua
Abstract : Hypoxia is a common feature of many solid tumors, including hepatocellular carcinoma (HCC). Hypoxia can promote tumor progression and induce radiation and chemotherapy resistance. As one of the major mediators of hypoxic response, hypoxia inducible factor-1 (HIF-1) has been shown to activate hypoxia-responsive genes, which are involved in multiple aspects of tumorigenesis and cancer progression, including proliferation, metabolism, angiogenesis, invasion, metastasis and therapy resistance. It has been demonstrated that a high level of HIF-1 in the HCC microenvironment leads to enhanced proliferation and survival of HCC cells. Accordingly, overexpression, of HIF-1 is associated with poor prognosis in HCC. In this review, we described the mechanism by which HIF-1 is regulated and how HIF-1 mediates the biological effects of hypoxia in tissues. We also summarized the latest findings concerning the role of HIF-1 in the development of HCC, which could shed light on new therapeutic approaches for the treatment of HCC.